Leading asymptotic terms of the three-body Coulomb scattering wave function - Mukhamedzhanov, A.; Kadyrov, Alisher; Pirlepesov , F. (American Physical Society, 2006)
The asymptotic wave function derived by Alt and Mukhamedzhanov [Phys. Rev. A 47, 2004 (1993)] and Mukhamedzhanov and Lieber [Phys. Rev. A 54, 3078 (1996)] has been refined in the region where the pair remains close to each other while the third particle is far away from them. The improved wave function satisfies the Schrdinger equation up to the terms of order O1/ 3, provides the leading asymptotic terms of the three-body scattering wave function with Coulomb interactions, and gives further insight into the continuum behavior of the three-charged-particle wave function, and helps to obtain the 3-3 scattered wave. This opens up further ways of solving and analyzing the three-body Schrdinger equation by numerical means.